The complete proof for the given parallelogram is given in the image attached below.
<h3>What is a Parallelogram?</h3>
A parallelogram is a quadrilateral whose opposite sides are parallel and also congruent to each other.
The complete proof would be as shown below:
1. ABCD is a parallelogram [given]
2. AB║CD [Definition of parallelogram]
3. ∠1 ≅ ∠2, ∠3 ≅ ∠4 [alternate interior angles theorem]
4. AB ≅ CD [Definition of parallelogram]
5. ΔABE ≅ ΔCDE [ASA]
6. AE ≅ CE, BE ≅ DE [CPCTC]
7. AC and BD bisects each other at E [definition of segment bisector]
Learn more about parallelogram on:
brainly.com/question/3050890
#SPJ1
Answer:
3.1
4.2
5.2
42
Step-by-step explanation: They’re congruent so just copy what the other triangle has all you had to do was find the radius.
F(x) = -34
Okx) = 2x
Both are correct
Hope this helps
Answers:
![\huge \boxed{T= \frac{P V}{n R} } \\ \\ \\ \\ \huge \boxed{W= \displaystyle \frac{1000C }{tc}}](https://tex.z-dn.net/?f=%5Chuge%20%5Cboxed%7BT%3D%20%5Cfrac%7BP%20V%7D%7Bn%20R%7D%20%7D%20%5C%5C%20%5C%5C%20%5C%5C%20%5C%5C%20%5Chuge%20%5Cboxed%7BW%3D%20%5Cdisplaystyle%20%5Cfrac%7B1000C%20%7D%7Btc%7D%7D)
![\rule[225]{225}{2}](https://tex.z-dn.net/?f=%5Crule%5B225%5D%7B225%7D%7B2%7D)
Step-by-step explanation:
<h2>8.</h2>
![P \cdot V = n \cdot R \cdot T](https://tex.z-dn.net/?f=P%20%5Ccdot%20V%20%3D%20n%20%5Ccdot%20R%20%5Ccdot%20T)
Dividing both sides by n · R:
![\displaystyle \frac{P \cdot V}{n \cdot R} =T](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7BP%20%5Ccdot%20V%7D%7Bn%20%5Ccdot%20R%7D%20%3DT)
<h2>9.</h2><h2 />
![\displaystyle C=\frac{Wtc }{1000}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20C%3D%5Cfrac%7BWtc%20%7D%7B1000%7D)
Multiplying both sides by 1000:
![1000C=Wtc](https://tex.z-dn.net/?f=1000C%3DWtc)
Dividing both sides by tc:
![\displaystyle \frac{1000C }{tc}=W](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B1000C%20%7D%7Btc%7D%3DW)
<h2 />
![\rule[225]{225}{2}](https://tex.z-dn.net/?f=%5Crule%5B225%5D%7B225%7D%7B2%7D)
Answer:
x = -1.4
Step-by-step explanation:
-3(x + 4) = 2x - 5
-3x + (-3*4) = 2x - 5
The mistake was in the above equation where -3 should be multiplied with 4.
-3x -12 = 2x -5
5 -12 = 2x+3x
-7 = 5x
x = -7/5 = - 1.4